Modification of peptide functionality during enzymatic hydrolysis of whey proteins. Issue 118 (13th November 2015) - Mohan, Aishwarya; Udechukwu, M. Chinonye; Rajendran, Subin R. C. K.; Udenigwe, Chibuike C.
Abstract : Enzymatic hydrolysis of whey proteins increased the reducing capacity and decreased reactive sulfhydryl (SH) content of the peptides. Hydrolysis yielded Maillard reaction products and the carbonyl compounds depleted SH by nucleophilic reaction. Abstract : Peptides derived from food proteins have shown promise as active ingredients for functional food formulation. Due to their reactivity, we evaluated the effects of conditions used for enzymatic hydrolysis of whey protein isolate (WPI) on the functionality of the resulting peptides. Free amino contents were increased when papain and alcalase were used for WPI hydrolysis, but the proteins (especially β-lactoglobulin) were mostly resistant to pepsin activity. The release of peptides during WPI hydrolysis was associated with increase in ferric reducing capacity, but there were also notable decreases in the redox-active sulfhydryl (SH) groups in the papain and alcalase reactions. Apparently, the reducing capacity of the hydrolysates was not dependent on their SH contents, which could have been utilised in disulfide formation. Moreover, considering that the WPI contained 1% lactose and other sugars, we observed that intermediate and advanced Maillard reaction products (MRPs) were formed during WPI hydrolysis, and this can directly impact both the reducing capacity and SH content of peptides. MRPs, such as reductones, can be highly antioxidative and possibly contributed to the reducing capacity observed for the protein hydrolysates, even with the depletion of the SH moieties. A model Maillard reaction with arginine, lactose or glucose, and reduced glutathione was used to confirm SH depletion in the presence of MRPs, and this was attributed to a nucleophilic reaction with carbonyl derivatives generated during the non-enzymatic glycation reaction. Although this can be an opportunity for generating strong redox-active ingredients, it presents some challenges particularly when the native structure of the peptides needs to be conserved for particular biological properties.